EFFECT OF CAFFEINE CONSUMPTION ON INTRAOCULAR PRESSURE AND RISK OF GLAUCOMA: A SYSTEMATIC REVIEW - Paramitha, Dewa Ayu Anggi; Azhari, Fierda Ovita; Anthea Casey; Eldinia, Lourisa Ruth (Majalah Oftalmologi Indonesia, 2024)
INTRODUCTION AND OBJECTIVES Glaucoma is one of the leading causes of blindness worldwide with intraocular pressure (IOP) as its main risk factor. Several studies have investigated the association between IOP and caffeine consumption with mixed results. This study aims to review whether caffeine consumption increases IOP thus, increases the risk of glaucoma. METHODS A comprehensive literature search was performed in 4 databases, including Pubmed, Proquest, ScienceDirect, and Cochrane. Last search was conducted on March 20, 2023. We include human studies investigating caffeine impact on IOP and/or glaucoma risk published in English with full text available from 2013 to 2023. The risk of bias was assessed with RoB 2.0 for crossover studies, NIH for cross-sectional and case-control studies. We present our results according to PRISMA guidelines. RESULT A total of 130.012 participants from 7 different studies were included in this review. Three crossover, 3 cross-sectional, and 1 case-control study were evaluated. This study involved a multi-racial population although Caucasian predominated. Five out of 7 studies exhibited a significant association (all p values <0.05) between caffeine consumption and increased risk of developing glaucoma. CONCLUSION Caffeine consumption generally shows a significant impact on developing risk of glaucoma and has been shown to increase IOP in acute settings, reported up to 90 minutes after consumption/ingestion. Limitations of this study include a small number of crossover participants and a high variability of participants (young healthy individuals and glaucoma patients). Further research is advised to investigate the association between caffeine consumption in a longer follow-up time and a more specific population.